On the Dual Stability of a Von Neumann Facet and the Inefficacy of Temporary Fiscal Policy - Yano, Makoto (Econometrica, 1998)
This study establishes two main results in a dynamic general equilibrium model. The first is to demonstrate the dual Liapounov stability of a von Neumann facet without the restrictive assumptions on the structure of underlying technologies adopted commonly in the optimal growth literature. The second is to demonstrate that a temporary change in fiscal policy has almost no effect on present and future consumption. While such a result has been discussed in the context of permanent income hypothesis, in this study it is proved in the dynamic general equilibrium framework under a set of basic assumptions of general equilibrium theory.